Developing Academic Writing Skills in EFL University Students Through Haiku Composition - Juan José Santillán-Iñiguez; Fabián Darío Rodas-Pacheco (Revista Electrónica Educare)
Background. Although there is empirical evidence to support the inclusion of poetry in the EFL classroom, the medium is rarely encountered in language learning environments. Aims. This study aimed to determine the influence of haiku composition tasks on developing academic writing skills of a group of TEFL majors at an Ecuadorian university. Method. The study was part of a larger research project (originally presented as a Master’s degree dissertation), developed under a mixed-method approach. This article reports the quantitative findings of the statistical analysis of results of two essay-based tests, administered before and after a six-week treatment that promoted haiku composition practices. Results. The findings determine a positive influence of haiku composition on the development of the academic writing skills of the participants in the study. Discussion. The main benefits of haiku composition in terms of academic writing skill development relate to the vocabulary enrichment and enhancement of linguistic competence, audience awareness, and writing process consciousness. These benefits are linked to the formal meter and reader-centeredness nature of haiku. The results encourage the inclusion of poetry-based creative writing tasks in EFL contexts; the evidence suggests that these activities are feasible and beneficial for motivated learners, particularly when framed within a student-centered process.